2017
DOI: 10.1590/1983-40632016v4746078
|View full text |Cite
|
Sign up to set email alerts
|

Performance of flood-irrigated rice as affected by residual rice straw1

Abstract: Rice is an economically important and widely consumed cereal that achieves high yields under flood-irrigated cultivation. However, the amount of residual straw from the previous year may influence its growth and yield. This study evaluated the performance of flood-irrigated rice as affected by residual rice straw, in a greenhouse. A completely randomized design, in a 5 x 4 x 2 factorial scheme, with four replications, was used. Treatments were obtained from a combination of five rice straw amounts (0 t ha-1, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many studies have been concerned with the influence of SR on crop growth and yield (Asten et al, 2005;Kaur and Mahal, 2017;Wang et al, 2018). For paddy fields, previous studies have investigated the impact of the amounts, application time, and burial depth of SR on rice (Oryza sativa L.) growth and yield (Beutler et al, 2017;Mi et al, 2018). It has been demonstrated that SR at the rate of < 7.5 t ha -1 can enhance rice plant height, number of tillers, and biomass production in the middle or late growth stages (Thuy et al, 2008;Han et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been concerned with the influence of SR on crop growth and yield (Asten et al, 2005;Kaur and Mahal, 2017;Wang et al, 2018). For paddy fields, previous studies have investigated the impact of the amounts, application time, and burial depth of SR on rice (Oryza sativa L.) growth and yield (Beutler et al, 2017;Mi et al, 2018). It has been demonstrated that SR at the rate of < 7.5 t ha -1 can enhance rice plant height, number of tillers, and biomass production in the middle or late growth stages (Thuy et al, 2008;Han et al, 2012).…”
Section: Introductionmentioning
confidence: 99%